2016
DOI: 10.1101/069708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The large majority of intergenic sites in bacteria are selectively constrained, even when known regulatory elements are excluded

Abstract: There are currently no broad estimates of the overall strength and direction of selection operating on intergenic variation in bacteria. Here we address this using large whole genome sequence datasets representing six diverse bacterial species; Escherichia coli , Staphylococcus aureus, Salmonella enterica , Streptococcus pneumoniae , Klebsiella pneumoniae , and Mycobacterium tuberculosis . Excluding M. tuberculosis , we find that a high proportion (62%79%; mean 70%) of intergenic sites are selectively constrai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This is presumably because a REPIN insertion into a gene would immediately destroy the open reading frame of the gene, which would have detrimental fitness effects for the host. To estimate the proportion of the genome that is permissive of REPIN insertion, we can rely on recent estimates of neutrally evolving sites in the extragenic space of a bacterial genome ( Thorpe et al 2016 ). If these estimates are similar among bacteria and also hold for REPIN insertions, then it is safe for REPINs to transpose into ∼4% of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…This is presumably because a REPIN insertion into a gene would immediately destroy the open reading frame of the gene, which would have detrimental fitness effects for the host. To estimate the proportion of the genome that is permissive of REPIN insertion, we can rely on recent estimates of neutrally evolving sites in the extragenic space of a bacterial genome ( Thorpe et al 2016 ). If these estimates are similar among bacteria and also hold for REPIN insertions, then it is safe for REPINs to transpose into ∼4% of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Salmonella Typhimurium, Pseudomonas aeruginosa, S. aureus, and Mycobacterium tuberculosis, have demonstrated that some genetic variations in IGRs are not neutral and mutations in IGRs may have an adaptative and evolutionary significant role in connection to bacterial pathogenesis, making its study necessary (Khademi et al, 2019;Osborne et al, 2009;Thorpe et al, 2016Thorpe et al, , 2017.…”
Section: Evolution and Identification Of Pathogenic Staphylococcus Au...mentioning
confidence: 99%
“…However, again, these epidemiological approaches do not consider the changes that take place in the IGRs as possible sources of variation that make some strains more likely to cause PJI. In this regard, recent studies have shown that changes in IGRs are not necessarily silent (Thorpe et al, 2016(Thorpe et al, , 2017. Ma et al observed an accumulation of SNPs in IGRs adjacent to genes encoding surface adhesins during the PJI outcome (Ma et al, 2021).…”
Section: Comparison Of the In Vivo Colonization Capacity Of S Aureus ...mentioning
confidence: 99%